2014
DOI: 10.1093/icc/dtu019
|View full text |Cite
|
Sign up to set email alerts
|

Quantity or quality? Knowledge alliances and their effects on patenting

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Studying the technological relevance of the 1 patented inventions, Vanhaverbeke, Beerkensand, and Duysters (2007) find a positive relationship between technology alliances and patent citations. Finally, Hottenrott and Lopes-Bento (2015) argue that the type of alliance may affect the ability and the incentives to patent, i.e., patent quality and quantity, differently.…”
Section: Gains From Collaborationmentioning
confidence: 99%
“…Studying the technological relevance of the 1 patented inventions, Vanhaverbeke, Beerkensand, and Duysters (2007) find a positive relationship between technology alliances and patent citations. Finally, Hottenrott and Lopes-Bento (2015) argue that the type of alliance may affect the ability and the incentives to patent, i.e., patent quality and quantity, differently.…”
Section: Gains From Collaborationmentioning
confidence: 99%
“…Similarly, Van Ophem et al (2001) find that firms participating in research partnerships file more patents than firms focusing on internal R&D. Branstetter and Sakakibara (2002) find similar results for firms in government-sponsored research consortia in Japan. Czarnitzki and Fier (2003) and Czarnitzki et al (2007) show that collaborating firms in Germany are more likely to patent than non-collaborating firms and Hottenrott and Lopes-Bento (2014b) argue that the type of alliance may affect the ability and the incentives to patent, i.e., patent quality and quantity, differently.…”
Section: Gains From Collaborationmentioning
confidence: 99%
“…At least part of the knowledge has to be revealed to the consortium partners. Collaborating firms may transmit not only codified but also tacit knowledge to the partner so that leakage risks go beyond the joint project (Hottenrott and Lopes-Bento 2014b). Indeed, partnerships bear the inherent risk of freeriding, where one associate tries to absorb the maximum knowledge from the other while concealing its own efforts (see e.g., Shapiro and Willig 1990;Baumol 1993;Kesteloot and Veugelers 1995).…”
Section: Pains From Collaborationmentioning
confidence: 99%
“…Each # Symbol in our paper means the number of variable (e.g., (9) in Table 3 is the number of patents). The table shows that an average co-invention network has about 2600 inventors, and they file a similar number of patents.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Indeed, numerous previous studies found that R and D alliances are used as an instrument by firms to acquire new skills and to source specialized know-how (see [9] for a nice review). However, these studies were interested in the effects of collaborative R and D on subsequent innovation performance, without putting emphasis on micro-level interactions of how individual inventors collaborate and which co-working structures are more productive.…”
Section: Introductionmentioning
confidence: 99%